(untitled) (Libellarium: journal for research in the field of information and related sciences, 2022)
The aim of the paper is to highlight the changing role of archives and to use the case study to indicate the lacking communication with students due to the absence of PR activities, as well as to point to the difficulties of access to digital archival materials needed for student research. Using PR strategies the archives can sensitise the public for its material through different public programmes, exhibitions and fostering goodmedia relations. The archives try to develop good relations with target groups, in this case with students as potential users, taking into consideration their research needs and materials they are interested in. Research findings on student needs for archival data are extremely rare, even in recent American research. Therefore, we conducted this research using a questionnaire for students of four departments of the University of Zadar (geography, history, art history, tourism and communication), who were users of the State Archives in Zadar. The research results show whether the subjects use archival material, for what purposes, and what other resources they used prior to archival material. It also provides information on the level of familiarity with online archival material and use of web pages with archival resources. We can conclude that the students in Zadar are not well acquainted with the digital resources and use them rarely for their research purposes. The situation can be improved by having the State Archives in Zadar take a more proactive role in identifying target groups of students, their user profiles, difficulties they face, and by allowing a more flexible access to archival material. In addition to goo d relations with the Department of Information Sciences, the Archives should foster links with other departments and include them in planning and implementation of their programmes.